Acute and mid-term outcome of ethanol infusion of vein of Marshall for the treatment of perimitral flutter. Issue 8 (29th June 2020) - Takigawa, Masateru; Vlachos, Konstantinos; Martin, Claire A; Bourier, Felix; Denis, Arnaud; Kitamura, Takeshi; Cheniti, Ghassen; Lam, Anna; Martin, Ruairidh; Frontera, Antonio; Thompson, Nathaniel; Massoullié, Grégoire; et al.
Abstract: Aims : We hypothesized that an epicardial approach using ethanol infusion in the vein of Marshall (EIVOM) may improve the result of ablation for perimitral flutter (PMF). Methods and results : We studied 103 consecutive patients with PMF undergoing high-resolution mapping. The first 71 were treated with radiofrequency (RF) ablation alone (RF-group), and the next 32 underwent EIVOM followed by RF on the endocardial and epicardial mitral isthmus (EIVOM/RF-group). Contact force was not measured during ablation. Acute and 1-year outcomes were compared. Flutter termination rates were similar between the RF-group (63/71, 88.7%) and EIVOM/RF-group (31/32, 96.8%, P = 0.27). Atrial tachycardia (AT) terminated with EIVOM alone in 22/32 (68.6%) in the EIVOM/RF-group. Bidirectional block of mitral isthmus was always achieved in the EIVOM/RF-group, but significantly less frequently achieved in the RF-group (62/71, 87.3%; P = 0.05). Median RF duration for AT termination/conversion was shorter [0 (0–6) s in the EIVOM/RF-group than 312 (55–610) s in the RF-group, P < 0.0001], as well as for mitral isthmus block in the EIVOM/RF-group [246 (0–663) s] than in the RF-group [900 (525–1310) s, P < 0.0001]. Pericardial effusion was observed in 1/32 (3.2%) in EIVOM/RF-group and 5/71 (7.0%) in RF-group ( P = 0.66); two in RF-group required drainage and one of them developed subsequent ischaemic stroke. One-year follow-up demonstrated fewer recurrences in the EIVOM/RF-group [6/32 (18.8%)] than in the RF-group [29/71 (40.8%), P = 0.04]. By multivariate analysis, only EIVOM was significantly associated with less AT recurrence (hazard ratio = 0.35, P = 0.018). Conclusion : Ethanol infusion in the vein of Marshall may reduce RF duration required for PMF termination as well as for mitral isthmus block without severe complications, and the mid-term outcome may be improved by this approach. Graphical Abstract: